Alcune implicazioni e problemi bioetici della diagnosi prenatale - Fabó, Fernando (Studia Bioethica, 2009)
In the first part of this article a general panorama of the techniques of prenatal diagnosis is defined and presented. Then a justification for the lawfulness of each is seen in the light of the advances of fetal medicine. The validity of PDG is strongly questioned and some clarification is given to points relative to the medical indications commonly given. In the second part, the bioethical aspects are treated further, explaining the ethical principles of a prenatal diagnosis that is respectful of our little patient ie. positive ethical value of the diagnosis; therapeutic proportionality; informed consent; responsibility-freedom. Conscientious objection is then highlighted and some cases are presented that evidence juridical-legal problems related with prenatal diagnosis. The conclusions direct towards a new focus on the prevention of genetic illnesses and malformations.